Compact Totally Real Minimal Submanifolds in a Bochner-Kaehler Manifold - Yüzbaşı, Zühal Küçükarslan; Bektaş, Mehmet; Yılmaz, Münevver Yıldırım (Emrah Evren KARA, 2018)
In this paper, we establish the following results: Let $M$ be an $% m-$dimensional compact totally real minimal submanifold immersed in a locally symmetric Bochner-Kaehler manifold $\tilde{M}$ with Ricci curvature bounded from below. Then either $M$ is a totally geodesic or \begin{equation*} \inf r\leq \frac{1}{2}\left( \frac{1}{2}m\left( m-1\right) \tilde{k}-\frac{1% }{3}\left( m+1\right) \tilde{c}\right), \end{equation*}% where $r$ is the scalar curvature of $M.$
Keywords: Mathematical Sciences; Matematik